Increased Serum Concentrations of TNF-Like Weak Inducer of Apoptosis Predict Higher 28-Day Mortality in Patients with Sepsis. (10th January 2019) - Guo, Ying; Ren, Manyi; Ge, Lili; Sun, Chao; Li, Rui; Ma, Cheng'en; Sui, Shujian
Abstract : We performed the current study to explore potential predictive value of serum Tumor Necrosis Factor- (TNF-) like weak inducer of apoptosis (TWEAK) concentrations for 28-day mortality in patients with sepsis. Adult septic patients (age≥18 years) admitted to a general ICU between November 2016 and October 2017 were consecutively included in our prospective observational study. TWEAK concentrations were detected in septic patients and healthy controls. Dynamic changes of TWEAK concentrations between 1st day and 3rd day of admission to ICU (ΔTWEAK concentrations) were also measured. A total of 79 septic patients were included and 19 of them (24.1%) died after a follow-up period of 28 days. We identified arterial lactate, NT-proBNP, and male gender as independent factors for 28-day mortality of patients with sepsis. The serum levels of TWEAK were significantly lower in septic patients compared to controls (417.4 ± 196.7 pg/ml versus 1243.8 ± 174.3 pg/ml, p <0.001). We found a positive correlation between TWEAK concentrations and SOFA score (Spearman correlation coefficient 0.235, p =0.037). Area under the receiver operating characteristic curve (AUROC) of ΔTWEAK concentrations for 28-day mortality was 0.754 (95% CI 0.645–0.844). We also evaluated the diagnostic performance of combinative index (ΔTWEAK concentrations and lactate) and obtained an AUROC of 0.860 (95% CI 0.763-0.928). In conclusion, our study found lower TWEAK concentrations in septic patients than those in healthy controls. Furthermore, the increased TWEAK concentrations during disease process predict higher 28-day mortality in septic patients. Dynamic changes of TWEAK should be an important supplement for current prognostic markers.